PATRIOTISM IS LOVE FOR THE MOTHERLAND, DEVOTION TO YOUR FATHERLAND - Oybek Kahramonovich Mirzoraximov (Western European Studies, 2024)
The article provides information about the concept of "Patriotic education" - about the education of a citizen and patriot who has high social activity, civic responsibility, spirituality, has positive values and qualities, and is able to demonstrate them in the interests of the Fatherland.
Keywords: Spirituality; citizenship; patriotism